A99 RESCUING TTC7A MUTANT PHENOTYPES ASSOCIATED WITH VERY EARLY ONSET INFLAMMATORY BOWEL DISEASE (VEO-IBD). (1st March 2018) - Jardine, S; Leung, G; Guo, C; Murchie, R; Dhingani, N; Warner, N; Pan, J; Muise, A
Abstract: Background: Very early onset inflammatory bowel disease (VEOIBD) is a severe disease presenting in children <6 years. Patients with TTC7A mutations present with apoptotic enterocolitis, disrupted intestinal architecture, multiple intestinal atresias, and/or combined immunodeficiency. There are few effective treatment options for these patients, and infant fatality is common. Rare autosomal recessive variants for tetratricopeptide repeat domain 7A (TTC7A) have been uncovered in the most severe forms of VEOIBD. The role of TTC7A in the pathogenesis of VEOIBD is largely unknown. Aims: The rising prevalence of IBD in Canada is driven by the rapidly increasing incidence (~60%) in children. Compounded with poor responses to standard IBD therapies, the need for therapies motivates researchers to seek effective treatment options. We hypothesize that TTC7A dysfunction results in aberrant intestinal phenotypes related to VEO-IBD. My research aim is to define TTC7A mutant phenotypes in cell-based and zebrafish models; thus, allowing for phenotypic screening and discovery of drugs for use in clinical settings. The overall research goal is to identify compounds that can rescue aberrant phenotypes induced by the TTC7A defect via high throughput drug screening. Since research on TTC7A's function is scarce, identifying drugs with known targets may provide some insight into TTC7A's cellular functions, and in VEO-IBD as a whole. Methods: Mutant phenotypes were characterized using CRISPR engineered TTC7A knockout HAP1 cells. Assays revolving around apoptosis and cell adhesion were used in a manner amenable to high throughput screening (HTS). For example, 96-well fluorescent and luminescent assays using caspase 3 /7 luciferases. TTC7A mutant zebrafish with fluorescently stained GI tracts allowed for peristaltic activity analyses. HTS using libraries containing FDA approved drugs identified drugs that could rescue TTC7A-related aberrant phenotypes Results: Aberrations in a range of phenotypes were observed in TTC7A i n vitro models including round and small morphologies, altered f-actin organization, poor adhesion, compromised viability, and increased susceptibility to apoptosis. Homozygous TTC7A zebrafish show reduced gut motility, narrow intestinal lumens, and increased apoptotic cells. Drug screening has identified several (hits) drugs capable of rescuing TTC7A phenotypes. These drugs will be validated in orthogonal assays as well as in patient derived intestinal organoids. Conclusions: Defining the TTC7A mutant phenotype has provided targets for identifying drugs for use in clinical settings. Furthermore, these findings could elucidate the functional pathways of this relatively uncharacterized protein. Drugs capable of rescuing TTC7A defects could increase patient prognosis and uncover functional pathways contributing to VEOIBD. Funding Agencies: CIHR